Extraction and properties of Nile Tilapia myofibrillar proteins for edible films - Quintero, Ednelí Soraya Monterrey; Sobral, Paulo José do Amaral (Pesquisa Agropecuaria Brasileira, 2000)
The elaboration of edible films based on biopolymers, implies the knowledge of physicochemical properties of macromolecules. The objectives of this work were to describe a methodology of preparing Nile Tilapia myofibrillar proteins and study the properties related to formation and characterization of edible film elaborated with these proteins. Freshly slaughtered ground Nile Tilapia (Oreochromis niloticus) muscle was washed and processed until the formation of a homogeneous paste. Evolution of protein fractions during processing was followed by scanning differential calorimetry. Solubility of freeze-dried myofibrillar proteins was studied as a function of pH (2-7). Identification of protein fractions and that of the composition of amino acids were accomplished by SDS-PAGE and ion-exchange chromatography, respectively. Biofilms, thus formed, were submitted to puncture, solubility and scanning electron microscopy tests. The sample of freeze-fried proteins, constituted only of myofibrillar proteins, presented maximum solubility (96.9%), at pH around 3 and a high ionic interaction potential (74.4 kJ/100 kJ). Nile Tilapia myofibrillar protein based biofilms were not very soluble (lower than 20 g/100 g dry matter). Glycerol strongly influenced mechanical as well as solubility properties of biofilms.